Total Talar replacements, short-medium term case series, South Africa, 2019 - Abramson, Michael James (Division of General Surgery, 2022)
Background: There are few surgical options available to manage complex talar pathology that result in predictably acceptable functional and patient satisfaction scores. Recently, the total talar replacement has gained popularity as a viable option. This study presents the clinical outcomes of the first case series of total talar replacements in South Africa. Methodology: A retrospective review of prospectively collected data of eight consecutive patients who underwent a total talus replacement between July 2014 and August 2018 was performed. The American Orthopaedic Foot and Ankle Hindfoot Score (AOFAS) was used to assess clinical functional outcome and the Short Form36 satisfaction index (SF-36) was used to assess patient satisfaction. Patient demographics as well as data on pathology, range of motion, gait analysis and radiological outcomes were included. Results: The average age was 46 years (range, 23 to 71). Pathologies included trauma, avascular necrosis and tumours. Average followup time was 23 months (range, 12 to 49). The mean AOFAS score was 79.25 (range, 69 to 88) and the mean SF36 was 83.25. (range, 60 to 93). No complications or revision surgeries have been performed to date. Seven patients demonstrated a mildly abnormal gait pattern with one in the moderate category. One patient showed radiological changes of minor tibial wear, however this was the patient with the longest followup time (49 months) and he remained symptom free. Conclusion: Total talar replacements are a viable surgical option in appropriately selected patients with end stage talar pathology in the short to medium term, without compromising future salvage options.